Coral reef fisheries of the Mzeina Bedu in South Sinai - Poonian, Christopher Narinder Singh Poonian (2020)
Coral reef ecosystems around the world are declining as a result of human impacts including overfishing, pollution and climate change. The coral reefs of South Sinai are significant because of their unique biodiversity, the income that they generate for Egypt through diving tourism and their importance as traditional fishing grounds for the Mzeina Bedu. This PhD takes a multidisciplinary approach to evaluate the status of coral reefs in South Sinai, with particular emphasis on Bedouin fishers and their fisheries. In Chapter 1, I examine the importance of culture and traditional knowledge in the successful management of coral reefs and natural resources in general. In Chapter 2, I focus on the Bedouin tribes of South Sinai to understand their history and socioeconomic status; investigating their fishing techniques and sites as well as their traditional understanding of coral reef biodiversity and ecology. Chapter 3 focusses on the ecological status of finfish populations at sites along the South Sinai coastline, evaluating the status of stocks and potential Bedouin fishery impacts. Chapter 4 examines the invertebrate fishery, which is mainly practised by Bedouin women and targets Tridacna clams. Chapter 5 takes a fishery-dependent approach to assess the catch of Bedouin fishers, to understand important biological and socioeconomic parameters that influence the fishery. In Chapter 6, I use statistical modelling techniques on long-term coral reef ecosystem data sets from the study area to analyse longer-term trends in the ecological status of reefs in South Sinai and likely causes for these trends. Coral reefs provide income, tourism, food and coastal protection to local communities and indigenous people throughout the tropics. The socio-cultural facets of the Mzeina Bedu have been inextricably connected to the reefs and associated fisheries of South Sinai for generations. However, exploited finfish and invertebrate communities have declined in both size and abundance with increased fishing pressure, resulting in ecosystem-wide impacts. The Mzeina themselves should be integral to any proposed fisheries monitoring or management initiatives, and technological approaches may provide useful cost-effective tools. Fisheries ecosystem-level declines have been apparent over at least the last decade and sustained monitoring is essential to ensure that the impact of management initiatives may be measured. If urgent collaborative management and enforcement actions are implemented alongside a programme to develop livelihood opportunities for the Mzeina, the reefs of South Sinai could return to a state that supports both the socioeconomic needs of the Bedu and continues to generate substantial tourism income.